Stock Liquidity and Stock Return - Violita, Cynthia Eka (Ekspektra : Jurnal Bisnis dan Manajemen, 2019)
This study aims to examine and analyze the effect of stock liquidity on stock returns on manufacturing companies listed on the Indonesia Stock Exchange. This study uses two control variables namely size and age and the study period from 2013 to 2017. The type of research used is quantitative, while the sample of this study are all manufacturing companies listed on the Indonesia Stock Exchange from 2013 to 2017. The method of determining the sample used is used is purposive sampling. The procedure of data collection in this research is the documentation method. The intended documentation method is collecting secondary data from the company's financial statements. Data analysis techniques used in this study were multiple linear regression, t test, and the coefficient of determination. The results showed that stock liquidity had a positive and significant effect on stock returns. While growth opportunity have a significant positive effect on stock returns.